√1+sin theta/√1-sin theta =cos theta/1-sin theta
Attachments:
![](https://hi-static.z-dn.net/files/d36/7d93204548e0c65aadda49f0fe59d56b.jpg)
Answers
Answered by
0
Step-by-step explanation:
given that ;
= √[(1+ sin theta)/ (1- sin theta )]
by rationalising the numerator
we get ;
= √[(1- sin^2 theta)/( 1- sin theta )^2]
= cos theta /(1- sin theta )
Answered by
0
Answer:
Your answer attached in the photo
Attachments:
![](https://hi-static.z-dn.net/files/daf/b60a57389fbaefa10ac2c6f3f50962e5.jpg)
Similar questions